Times of memory, times of victims (2008)
This article illustrates the plurality of subjectivities linked to the memory of victims. The author explores the stories of three well known survivors of the Nazi concentration camps: Primo Levi, Jean Améry and Jorge Semprún. Starting from there, the text deepens in the survivor’s profiles and analyzes each testimony to present this way a series of considerations, with a high pedagogic orientation, aiming at the generation of social conscience in view of the complexity of memory in connection with the victims of a conflict and thus preventing further errors in its treatment.